Epidemiological features of uterine fibroid-associated imaging changes in Chinese women of reproductive age: a retrospective study - Wei Xu; Lijun Zhang; Qiuling Shi; Fan Xu; Ke Chen; Yanyan Huang; Ruoyan Gong; Yang Pu; Xueyao Su; Jiayuan Zhang; Bingqian Zhou (BMJ Open)
Objectives To investigate uterine fibroid (UF)-associated imaging changes, and their prevalence, incidence and potential risk factors in the Chinese population.Design This was a retrospective observational study using health examination data.Setting A physical examination centre in Nanchong, China, between October 2017 and December 2020.Participants A total of 33 915 Chinese women older than 15 years of age underwent uterine imaging during the study period.Primary and secondary outcome measures This study identified entries of UF-associated imaging changes through a two-round expert consultation and calculated prevalence and incidence of UF-associated imaging changes. Logistic regression estimated the association (OR, 95% CI of body mass index, high blood pressure (HBP), blood lipid profile, and fasting blood glucose level) with UF-associated imaging changes. Age-stratified (≤40 years and >40 years) risks were ascertained.Results Besides the entry ‘Potential UF’, 17 other entries of UF-associated imaging changes screened by the expert consultation were included, involving a total of 46 864 records (n=33 915), and crude prevalence=25.18%; crude incidence density/1000-woman-years=63.28. Incidence and prevalence increased with age during reproductive age (15–49 years) and decreased thereafter. The greatest burden was in women aged 40–54 years, the prevalence was 38.60%–45.38% and the incidence was 14.73%–17.96%. In the incident younger population (age ≤40 years), overweight (OR: 1.48, 95% CI 1.03 to 2.14) and HBP (OR: 2.16, 95% CI 1.10 to 4.24) were associated with a higher risk for UF-associated imaging changes; in the >40 years group, no association was observed.Conclusion UF incidence and prevalence in Asians were higher than previously reported, showed age-related increase in reproductive age, and UF incidence increased with overweight and HBP in ≤40-year-old participants. Variation in UF burden and factors with higher risk noted in different age ranges, and the correlations identified in younger women make it possible for early preventive measures for women with a higher risk of UF.